Comparison of immune responses to SARS-CoV-2 spike following Omicron infection or Omicron BA.4/5 vaccination in kidney transplant recipients - Tometten, Inga; Brandt, Tobias; Schlotz, Maike; Stumpf, Ricarda; Landmann, Sinje; Kantauskaite, Marta; Lamberti, Joshua; Hillebrandt, Jonas; Müller, Lisa; Kittel, Margarethe; Ivens, Katrin; Gruell, Henning; et al. (Frontiers in Immunology, 2025)
BackgroundThe emergence of novel SARS-CoV-2 variants challenges immunity, particularly among immunocompromised kidney transplant recipients (KTRs). To address this, vaccines have been adjusted to circulating variants. Despite intensive vaccination efforts, SARS-CoV-2 infections surged among KTRs during the Omicron wave, enabling a direct comparison of variant-specific immunity following-vaccination against Omicron BA.4/5 or Omicron infection in KTRs.Methods98 SARS-CoV-2 naïve KTRs who had received four vaccine doses were studied. Before and after a 5th antigen exposure, either via the bivalent vaccine composed of ancestral SARS-CoV-2 and Omicron BA.4/5 (29 KTRs) or via natural infection with Omicron (38 BA.4/5, 31 BA.1/2), spike-specific T cells were quantified using Elispot and serum pseudovirus neutralizing activity was assessed against the ancestral Wuhan strain, BA.5 and XBB.1.5.ResultsCompared to BA.4/5 vaccination, spike-specific T-cell responses and neutralization activity were higher up to six months post-Omicron infection and reached levels similar to healthy controls. Vaccinated KTRs showed modestly boosted neutralization activity against the Wuhan strain and BA.5, but not XBB.1.5. Baseline immunity correlated with immune responses three months post-vaccination and post-infection, indicating a predictive value for peak immune responses. Tixagevimab/Cilgavimab treatment was associated with robust neutralization of the Wuhan strain, but ineffective against XBB.1.5.ConclusionThe BA.4/5 vaccine improved neutralizing activity against the BA.4/5 variant, but not against the subsequently circulating XBB.1.5 variant in KTRs. Conversely, omicron infection boosted T cells and humoral responses more effectively, showing efficacy against XBB.1.5. These findings suggest that infection-induced immunity associates with greater protection than vaccination against future variants in KTRs.